Bacterial and Archaeal Diversity and Abundance in Shallow Subsurface Clay Sediments at Jianghan Plain, China - Song, Dandan; Jiang, Zhou; Ma, Teng; Dong, Yiran; Shi, Liang (Frontiers in Microbiology, 2020)
Clay layers are common in subsurface where microbial activities play an important role in impacting the biogeochemical properties of adjacent aquifers. In this study, we analyzed the community structure and abundance of bacteria and archaea in response to geochemical properties of six clay sediments at different depths in a borehole (112°34'0''E, 30°36'21''N) of Jianghan Plain (JHP), China. Our results suggested that the top two clay layers were oxic, while the remaining bottom four clay layers were anoxic. Both high-throughput sequencing and qPCR of 16S rRNA gene showed relatively high abundance of archaea (up to 60%) in three of the anoxic clay layers. Furthermore, microbial communities in these clay sediments showed distinct vertical stratification, which may be impacted by changes in concentrations of sulfate, HCl-extractable Fe2+ and total organic carbon (TOC) in the sediments. In the upper two oxic clay layers, identification of phyla Thaumarchaeota (11.2%) and Nitrosporales (1.2%) implied nitrification in these layers. In the two anoxic clay layers beneath the oxic zone, high abundances of Anaeromyxobacter, Chloroflexi bacterium RBG 16_58_14 and Deltaproteobacteria, suggested the reductions of nitrate, iron and sulfate. Remarkably, a significant portion of Bathyarchaeota (~25%) inhabited in the bottom two anoxic clay layers, which may indicate archaeal anaerobic degradation of TOC by these organisms. The results of this study provide the first systematic understandings of microbial activities in subsurface clay layers at JHP, which may help develop microorganism-based solutions for mitigating subsurface contaminations.